2019
DOI: 10.1186/s13048-019-0556-7
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone suppresses excessive follicular development in murine preantral follicles

Abstract: Polycystic ovary syndrome (PCOS) is an endocrine disease that is common in women in their reproductive period. Patients with this disease suffer from anovulation and hyperandrogenism. Ovulation induction with exogenous gonadotropin often causes ovarian hyperstimulation syndrome because many small antral follicles pause in their growth. Treatment with insulin sensitizers is reportedly effective for both anovulation associated with PCOS, and suppression of excessive follicular growth; however, the underlying mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Currently, the most commonly used method for in vitro culture of mouse preantral follicle is the two-dimensional droplet method. [1][2][3] The 80-180 μm preantral follicle is selected for in vitro culture, 13,22,23 and the commonly used r-FSH concentration is 10 mIU/ mL or 100 mIU/mL. 13,23,24 Under the same conditions, the average in vitro maturation rate of follicular oocytes is 60%-70%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the most commonly used method for in vitro culture of mouse preantral follicle is the two-dimensional droplet method. [1][2][3] The 80-180 μm preantral follicle is selected for in vitro culture, 13,22,23 and the commonly used r-FSH concentration is 10 mIU/ mL or 100 mIU/mL. 13,23,24 Under the same conditions, the average in vitro maturation rate of follicular oocytes is 60%-70%.…”
Section: Discussionmentioning
confidence: 99%
“…al also showed that FSH could promote the survival of preantral follicles with a diameter of 95-142 μm in mice. 21 Recently, preantral follicles with a diameter of 80-180 μm are often selected and used for in vitro culture, 13,22,23 and follicles in this diameter range include grade II, III, IV, and V follicles. The different grades of follicles have different amounts of granulosa cells and different sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that both endogenous and exogenous sources of androgen excess may directly contribute to the development of polycystic ovary morphology [91]. Table 3 has summarized the various rodent primary follicle cultures that have been used to investigate the stimulation of follicle growth by androgens [84,90,[92][93][94]. Among the strains of rodents provided by major suppliers, C57BL/6 and ICR mice are commonly used in studies related to aging, toxicology, pathology, and physiology [95].…”
Section: Mouse Primary Follicle Culturesmentioning
confidence: 99%
“…It has been proven that increased insulin levels or IR can cause hypothalamic-pituitary-ovarian axis dysfunction, thereby inhibiting the synthesis and expression of sex hormone-binding globulin and indirectly causing increased levels of androgens in the body (6). In turn, high androgen concentrations cause IR, inhibiting follicular development and maturity, thereby affecting the quality of oocytes (7). In the granulosa cells of atretic follicles in patients with PCOS, IR-related insulin-like growth factors are abundantly expressed (8).…”
mentioning
confidence: 99%